VIRTUAL REALITY SCIENCE LEARNING WEBSITE - MUHAMAD BAIJURI, ZARITH NOR ATIQAH (IRC, 2020)
This dissertation report presents the study research of Virtual Reality Science Learning Website. First, children did not expose to the newest technology for online learning process. Parents nowadays prefer to let their kids watch cartoon on You Tube to learn something rather than using the online learning platform. By using You Tube, a strict supervision is needed because You Tube contain various type of videos from all around the world. To solve this, the identification of the importance of technology on science education learning is needed. The importance of education and knowledge in science and technology is vital for future development of the country. This will trigger the children interest in these domain at their early stage is definitely crucial. Hence the development of Virtual Reality Science Learning Website will be using the verified syllabus by government to ensure the kids can learn anytime and anywhere. This is indirectly will help those unfortunate kid who do not have chance to attend pre-school and do not have science educational resource at home. The website usability for kids will be tested after the development is done. The Virtual Reality Science Learning website will be tested by the preschools teachers. Questions in term of usability will be given to the teachers and they will rate it. The feedback received will be used to improve and test the system to ensure the website working smoothly. Virtual Reality Science Learning Website is an education science system specially made for young children. This system basically is a combination of education and technology. This education system give user a chance to choose whether to use it by browser or as a web application. It enables users to experience both applications view or desktop view version of a system. Virtual Reality Science Learning Website, focus on science learning for young children using the Animals lesson. This website contains three major lesson and three quiz which is Lesson 1: Introduction to Animal, Lesson 2: The Type of Animal and Lesson 3: Habitat of Animal. From all the research and requirement gathering, the user interface of this website will be attractive with colorful design, interesting cute character, virtual tour and the simplicity feature will ease.